Processes of intercultural education and indigenous self-segregation in the Aimaras of Puno, Perú - Bermejo Paredes, Saul; Maquera Maquera, Yanet Amanda; Bermejo Gonzáles, Luz Yohana (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of the study is to interpret from the Aymara thinking, how the processes of bilingual intercultural education (IBE) developed in rural schools in the Aymara area of Puno-Peru, generate the phenomenon of indigenous self-segregation after forty years. Self-segregation is not specified as a goal or objective by any EIB policy or program; It is conceived as a driving force for the construction of strategic alliances to conduct its own educational purposes, keeping the Aymara culture and language alive, without disassociating itself from national and world society. This has to do with a new and binding theme to redefine such as the education provided in indigenous populations. It is a qualitative-hermeneutic research work that, using the techniques of documentary analysis and in-depth interviews; the results are studied, through the content analysis process, fundamentally; allowing to establish as a conclusion that from the Aymara thinking the EIB only receives a symbolic value, it is perceived as a racist program which over time has caused a gradual linguistic displacement of the Aymara by the Spanish and the folklore of wisdom and Aymara culture; situation that simultaneously has made possible the emergence of indigenous self-segregation, as a strategy and rationale to redefine IBE, education in general and the livelihood of the Aymara nation.